2017
DOI: 10.1093/mnras/stx1168
|View full text |Cite
|
Sign up to set email alerts
|

Disc–jet coupling in low-luminosity accreting neutron stars

Abstract: In outburst, neutron star X-ray binaries produce less powerful jets than black holes at a given X-ray luminosity. This has made them more difficult to study as they fade towards quiescence. To explore whether neutron stars power jets at low accretion rates (L X 10 36 erg s −1 ), we investigate the radio and X-ray properties of three accreting millisecond X-ray pulsars (IGR J17511-3057, SAX J1808.4-3658 and IGR J00291+5934) during their outbursts in 2015, and of the non-pulsing neutron star Cen X-4 in quiescenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 135 publications
(197 reference statements)
4
70
0
Order By: Relevance
“…Alternatively, the X-ray wind itself could be responsible for boosting radio luminosity via wind-jet interaction. This was previously suggested as a possible explanation for the observed radio flares in SAX J1808.4−3658 (Tudor et al 2017). Such a scenario could also be a potential explanation for the large variability of the radio emission of IGR J17591−2342, which appears to be the brightest during the first three radio epochs.…”
Section: Radio-x-ray Relationmentioning
confidence: 57%
See 2 more Smart Citations
“…Alternatively, the X-ray wind itself could be responsible for boosting radio luminosity via wind-jet interaction. This was previously suggested as a possible explanation for the observed radio flares in SAX J1808.4−3658 (Tudor et al 2017). Such a scenario could also be a potential explanation for the large variability of the radio emission of IGR J17591−2342, which appears to be the brightest during the first three radio epochs.…”
Section: Radio-x-ray Relationmentioning
confidence: 57%
“…In the last few years, new and upgraded radio telescopes -like the Karl G. Jansky Very Large Array (VLA), the Australia Telescope Compact Array (ATCA), and MeerKAT -coupled with flexible X-ray observatories such as the Neil Gehrels Swift X-ray Telescope (Swift-XRT), have provided the sensitivity and rapid response required to probe a steadily increasing number of known Galactic NS-LMXBs. This includes accreting millisecond X-ray pulsars (AMXPs; Tudor et al 2017), where the accretion flow is channeled by the NS's magnetic field (producing coherent X-ray pulsations: e.g., Wijnands & van der Klis 1998; see Patruno & Watts 2012 for a review), as well as non-pulsing NS-LMXBs -both of which have been observed in the hard and soft X-ray spectral states (e.g., Gusinskaia et al 2017). NS-LMXBs have been observed during their bright (Xray luminosity LX ∼ 10 36−38 erg s −1 ) accretion outbursts (e.g., Migliari & Fender 2006), and as they fade back to quiescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light-green triangles mark known transitional millisecond pulsars (Hill et al 2011;Papitto et al 2013;Deller et al 2015;Bogdanov et al 2018). The deep-blue squares and pink stars show quiescent/hard-state NSs and accreting millisecond X-ray pulsars (AMXPs), respectively (Migliari & Fender 2006;Tudor et al 2017). The yellow triangles show upper limits of L R of two X-ray transients (Tetarenko et al 2016;Ludlam et al 2017).…”
Section: U18: a Hidden Msp?mentioning
confidence: 99%
“…Due to these time constraints and their relative radio faintness, only a few NS-LMXBs have been observed in the luminosity range LX < 10 36 erg s −1 . In the case of non-pulsating NS-LMXBs, these observations led exclusively to non-detections (Gusinskaia et al 2017;Tetarenko et al 2016;Tudor et al 2017). However, there are two classes that potentially stand out in this low X-ray luminosity regime (Gallo et al 2018): accreting millisecond Xray pulsars (AMXPs; systems that exhibit coherent millisecond X-ray pulsations as a result of accreting material channelling onto the magnetic polar caps of the NS; Wijnands & van der Klis 1998;Patruno & Watts 2012) and transitional millisecond pulsars (tMSPs; NSs that switch between rotation-powered radio millisecond pulsars and an accretiondisc state; Papitto et al 2013;Jaodand et al 2018).…”
Section: Introductionmentioning
confidence: 99%